IMPLEMENTASI PENEGAKAN HUKUM BERBASIS TEKNOLOGI INFORMASI TERHADAP PENGGUNAAN ELECTRONIC TRAFFIC LAW ENFORCEMENT BAGI PELANGGAR LALU LINTAS OLEH LEMBAGA KEPOLISIAN - Iqbal Arysepta Imam Mahbi; Nabila Annisa Fuzain; Rizky Wardana (Jurnal Hukum Lex Generalis, 2024)
Poor compliance with Law Number 22 of 2009 concerning Traffic and Road Transportation (UU LLAJ) indicates a lack of effectiveness in traffic law enforcement in Indonesia. The Indonesian National Police Regulation Number 8 of 2023 on Electronic System-Based Implementation currently governs ETLE (Electronic Traffic Law Enforcement) operations. Various AI technologies used in ETLE mechanisms include static, mobile, portable, drone, and face recognition systems. On toll roads, ETLE with Weigh-In-Motion (WIM) sensors is employed to address over-dimension and overloading (ODOL) trucks. The Traffic Law Enforcement Subdirectorate (Ditgakkum Subdit Dakgar) successfully increased ETLE enforcement by 35.7% in 2023. The types of ETLE are adapted to the specific needs of each region.